New species of Eidmanacris Chopard, 1956 from Brazil (Orthoptera: Phalangopsidae: Luzarinae) - De Campos, Lucas Denadai; Souza-Dias, Pedro G. B.; Nihei, Silvio Shigueo; De Mello, Francisco De A. G. [UNESP] (Magnolia Press, 2015)
With 15 described species, Eidmanacris is one of the largest Luzarinae genera from South America. In Brazil, 12 species occur in two large biomes, the Atlantic Forest and Cerrado. Here, we describe four new species of Eidmanacris from Brazil: E. bernardii Nihei & de Mello, n. sp., E. papaveroi Nihei & de Mello, n. sp., E. simoesi Nihei & de Mello, n. sp., and E. eliethae Nihei & de Mello, n. sp., from Cerrado (E. bernardii n. sp.), and the other from Atlantic Forest. The type material is deposited in the Museu de Zoologia da Universidade de Sao Paulo (MZSP) and the Zoology Department Insect Colletion (Colecao de Insetos do Departamento de Zoologia), Botucatu campus of Sao Paulo State University, UNESP.
Keywords: Grylloidea; Phalangopsidae; Taxonomy; new species; cricket